Assessment of Electrospinning Antioxidant Nanofibers in Skin Exposure to Oxidative Stress - Saba Kalantary; Farideh Golbabaei; Masoud Latifi; Mohammad Ali Shokrgozar; Mehdi Yaseri (Journal of Mazandaran University of Medical Sciences, 2020)
Background and purpose: Some skin injuries are caused by occupational skin exposures that are resulted from production of reactive oxygen species and oxidative stress (ROS). Thus, protecting the skin is a key issue. Recently, several surveys have introduced novel alternatives such as nanofibers for skin protection. In this research, Poly (ε-caprolactone) (PCL)/gelatin (Gt)/ Vitamin E (VE) was investigated as a nanofiber antioxidant protective layer in occupational skin exposures. Materials and methods: Vitamin E was combined with PCL/Gt nanofiber mats by electrospinning method. The diameter of nanofibers and chemical characteristics were determined using scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR). Adhesion characteristics and proliferation of human dermal fibroblast cells (HDFC) on nanofibers were analyzed by Methylthiazol Tetrazolium (MTT) assay. Finally, we studied the application of PCL/Gt/VE nanofibers against oxidation stress induced by tert-butyl hydroperoxide (t-BHP). Results: With increase in Vitamin E levels, the PCL/Gt/VE nanofibers were found to be thiner. The culture of HDF cells on nanofibers showed that adding Vitamin E to PCL/Gt mats caused increased attachment and proliferation of the cells. PCL/Gt/VE nanofibers significantly assisted human skin cells against ROS (P< 0.001). Conclusion: According to current study, PCL/Gt/VE nanofibers could be an appropriate candidate for protecting skin against ROS as a novel method to maintain workers’ health.